Optimisation of Proton‐Conducting sPEEK Membranes through a Thermal Treatment Method Monitored by Dielectric Spectroscopy. Issue 11 (15th March 2018) - Córdova‐Chávez, Miguel E.; Hernández, Marianella; Picken, Stephen J.; Kelder, Erik M.
Abstract: The Sulfonated Poly (Ether Ether Ketone) (sPEEK) is used in many of the developments of polymer electrolyte membranes for fuel cells. In this publication, it is proven that the water in the sPEEK membrane creates channels in the sulfonated clusters by interacting with the sulfonic groups, and changing the glass transition temperature (Tg) of the material. It is shown that, for conductivity, apart from water in the membrane, order is needed in the water channels because it has an impact on how fast the protons pass through the membrane. This research focuses on how various thermal treatment, performed under a pre‐stated conditioning; allow the free alignment of the inner phases, influencing their order. It is demonstrated how is possible to use of differential calorimetry, dielectric measurements and X‐ray to follow these changes, and how to used Broadband Dielectric Spectroscopy to forecast the most optimal and stable thermal treatment for the highest proton conduction in sPEEK. The methodology is also test successfully on a hybrid sPEEK/Boron Phosphate membrane. Abstract : Polymer Membranes capable of conducting protons are used in Fuel Cells, this membranes need to be able to create interconnected channels inside to move the protons from one side to the other. These channels need to have a medium to transport protons, which is usually water in an acidic medium. This works created a methodology to optimize these channels through thermal treatments after pre conditioning and followed these changes using Dielectric Measurements, X‐rays and Calorimetry.